Injection characteristics study of high-pressure direct injector for Compressed Natural Gas (CNG) using experimental and analytical method - Mohd Fadzil, Abdul Rahim; Zahari, Taha; Rizalman, Mamat (IOP Publishing, 2017)
The injection characteristics of direct injector affect the mixture formation and combustion processes. In addition, the injector is converted from gasoline operation for CNG application. Thus measurement of CNG direct injector mass flow rate was done by independently tested a single injector on a test bench. The first case investigated the effect of CNG injection pressure and the second case evaluate the effect of pulse-width of injection duration. An analytical model was also developed to predict the mass flow rate of the injector. The injector was operated in a choked condition in both the experiments and simulation studies. In case 1, it was shown that mass flow rate through the injector is affected by injection pressure linearly. Based on the tested injection pressure of 20 bar to 60 bar, the resultant mass flow rate are in the range of 0.4 g/s to 1.2 g/s which are met with theoretical flow rate required by the engine. However, in Case 2, it was demonstrated that the average mass flow rate at short injection durations is lower than recorded in Case 1. At injection pressure of 50 bar, the average mass flow rate for Case 2 and Case 1 are 0.7 g/s and 1.1 g/s respectively. Also, the measured mass flow rate at short injection duration showing a fluctuating data in the range of 0.2 g/s - 1.3 g/s without any noticeable trends. The injector model able to predict the trend of the mass flow rate at different injection pressure but unable to track the fluctuating trend at short injection duration.